(untitled) (Journal of Enam Medical College, 2017)
Background: Several behavioral factors, specially stress, eating behavior, and physical activity have been linked with adolescent obesity. In our country, mental health of adolescents is often neglected. So, we designed this study to describe the current perception of stress in Bangladeshi adolescent students. Objective: Aim of this study was to assess association between stress and body mass index of adolescents while controlling for physical activity and examining stress associated eating behavior. Materials and Methods: This cross-sectional study was carried out among 278 adolescent students during the period from January to December 2013. Data were collected through self-administered questionnaire which included physical activity questions, Dutch Eating Behavior Questionnaire (DEBQ), Adolescent stress questionnaire (ASQ) and standard anthropometric measurements and were analyzed statistically using SPSS version 21.0. Results: In this study majority of the respondents were males. Among the female respondents, about 12.23% were overweight and obese compared to their male peers (4.1%). The normal and high BMI adolescents in the study showed significantly different proportions regarding gender (p<0.001), fathers education (p=0.036) and smoking status (p=0.22). Findings in this study reveals negative correlation between physical activity score and body mass index (?=?0.15, p<0.05). Body mass index was found significantly correlated with all three DEBQ eating subscales the restraint score, emotional eating score (?=0.58 p<0.001), and external eating score (?=0.55, p<0.001). Based on sample data, the mean stress scores were due to home life (3.40±0.54), school performance (3.31±0.63), school attendance (2.42±0.87), romantic relationship (3.02±0.92), peer pressure (2.85±0.72), due to teacher interaction (2.89±0.56), future uncertainty (3.83±0.90), school/leisure conflict (3.55±0.68), financial pressure (2.99±0.79) and emerging adult responsibility (3.11±0.76). Majority of the respondents (86.7%) were highly stressed. The study identified gender (OR,19 with 95% CI; 4.7,90.6), Fathers education (OR,16 with 95% CI; 1.6,16), and stress contributed by school/leisure conflict (OR, 4 with 95% CI; 1.2,13.8) as significant predictors of adolescents BMI when adjusted for other factors. Conclusion: School/leisure conflict related stress was found associated with body mass index when adjusted for other factors. School is reported to be an important source of adolescent stress and should be the focus of stress management campaigns. J Enam Med Col 2017; 7(2): 77-85